To solve this system of equations, we can use the method of substitution.
From the second equation, we can rewrite it as:
32/x + 12y = 2.2
Next, we can multiply both sides of this equation by x to get rid of the fraction:
32 + 12xy = 2.2x
Now, we can rearrange this equation to solve for x:
2.2x - 12xy = 32
Factor out x:
x(2.2 - 12y) = 32
Divide both sides by (2.2 - 12y) to solve for x:
x = 32 / (2.2 - 12y)
Now, we can substitute this expression for x in the first equation:
13(32 / (2.2 - 12y)) + 22y = 1610
Multiply both sides of this equation by (2.2 - 12y) to eliminate the denominator:
13(32) + 22y(2.2 - 12y) = 1610(2.2 - 12y)
Simplify:
416 + 22y(2.2 - 12y) = 3542 - 19320y
Expand:
416 + 48.4y - 264y^2 = 3542 - 19320y
Rearrange this equation to form a quadratic equation:
264y^2 - 48.4y - 19320y + 3542 - 416 = 0
Combine like terms:
264y^2 - 19632y + 3126 = 0
Divide through the equation by 6 to simplify:
44y^2 - 3272y + 521 = 0
This is a quadratic equation that we can solve for y using factoring, completing the square, or the quadratic formula.
13×+22y = 1610
32/× +12y = 22/10
1 answer